PESANTREN DAN UPAYA DERADIKALISASI AGAMA - Mukodi, Mukodi (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2015)
The de-radicalization of Islam in Tremas Islamic boarding school was found to have its continuing momentums from generation to generation. Through cultural practices as: scientific culture, religious culture, social culture, and political culture the seeds of such de-radicalization were disseminated. However, the dynamic fluctuation of extremism both transnationally and internationally became a specific challenge. Furthermore, the massive development of Information and Communication Technology (ICT) significantly impacted on the mindset of Tremas boarding school community. Applying qualitative approach and phenomenological method, this article revealed how the religious de-radicalization in Tremas boarding school was knitted and framed in the practices of daily culture. Such practices were carried out in order to make Islamic generations may wisely behave and act. Moreover, Islam might ocupy as it should be, namely Islam as raḥmatan li ’l-‘ālamīn, love peace, promoting love and affection, as well as non-violence.***Deradikalisasi agama Islam di Pondok Tremas dari generasi ke generasi senantiasa menemukan momentum. Melalui praktik budaya Pondok Tremas yang meliputi: budaya keilmuan, budaya keagamaan, budaya sosial dan budaya politik benih-benih deradikalisasi agama Islam disemaikan. Namun demikian, pasang surut paham ekstremisme yang berkembang di transnasional, dan internasional menjadi tantangan tersendiri. Apalagi masifnya perkembangan media teknologi dan informatika berekses secara signifikan pada pola pikir warga Pondok Tremas. Dengan menggunakan pendekatan kualitatif, dan metode fenomenologi, artikel ini menjelaskan bagaimana deradikalisasi agama di Pondok Tremas dirajut, dan dibingkai dalam praktik-praktik budaya keseharian. Hal itu, dilakukan agar generasi Islam dapat bijak dalam bersikap dan bertindak. Lebih dari itu, agar agama Islam dapat menempati area yang semestinya, yakni agama raḥmatan li ’l-‘ālamīn, tanpa kekerasan, cinta perdamaian, dan mengedepankan cinta kasih.